Origin, characterization and fate of alpha smooth muscle actin-positive cells during lung development and disease - Moiseenko, Alena; Justus Liebig University Giessen (My University, 2017)
Alpha smooth muscle actin (ACTA2)-expression identifies pulmonary airway and vascular SMCs as well as alveolar myofibroblasts (MYFs). These cells are important for normal respiratory function and their dysregulation is associated with disease. Mesenchymal progenitors expressing fibroblast growth factor 10 (Fgf10), Wilm s tumor 1 (Wt1) or glioma-associated oncogene 1 (Gli1) contribute to SMC formation from early stages of lung development. However, their respective contribution and specificity to the SMC and alveolar MYF lineages remain controversial. In addition, the contribution of mesenchymal cells undergoing WNT signaling remains unknown. Using Fgf10CreERT2, Wt1CreERT2, Gli1CreERT2 and Axin2CreERT2 inducible driver lines in combination with a tdTomatoflox reporter line, the respective differentiation of each pool of labeled progenitor cells along the SMC and alveolar MYF lineages was quantified. The results revealed that while FGF10+ and WT1+ cells showed a minor contribution to the SMC lineage, GLI1+ and AXIN2+ cells significantly contributed to both the SMC and alveolar MYF lineages, but with very limited specificity. Lineage tracing using the Acta2-CreERT2 transgenic line showed that differentiated airway and vascular SMCs labeled at E11.5 do not expand significantly to give rise to new SMCs at E18.5. However, ACTA2+ cells from E15.5 label almost all SMCs in the lung at E18.5, as well as alveolar MYF progenitors in the lung parenchyma. FACS-based isolation of different subpopulations of ACTA2+ lineage-traced cells followed by gene arrays, identified transcriptomic signatures for alveolar MYF progenitors versus airway and vascular SMCs at E18.5. Our results establish a new transcriptional landscape for further experiments addressing the function of signaling pathways in the formation of different subpopulations of ACTA2+ cells.Contractile ACTA2+ cells called activated myofibroblasts (MYFs) are the main effector cells in idiopathic pulmonary fibrosis (IPF). IPF is characterized by excessive accumulation of activated MYFs and lung tissue scarring. Currently there is no effective treatment against IPF. Understanding the origin of the activated MYFs is of great interest. Using Acta2-CreERT2 transgenic line to label pre-existing ACTA2+ showed that pre-existing ACTA2+ airway and vascular SMCs do not give rise to activated MYF. During resolution of fibrosis, we show that activated MYFs lose ACTA2 expression and acquire lipofibroblast-like phenotype. Manipulating this phenotypic switch might offer new therapeutic opportunities for IPF patients.
Keywords: ddc:610